FATIGUE PERFORMANCE ANALYSIS OF VASCULAR STENT BASED ON TWO-WAY FLUID-SOLID COUPLING (MT) - YANG Hang; MUHETAER KeLiMu; WU Chuan; YANG HaiKun (Jixie qiangdu)
In order to evaluate the influence of the thickness of the stent on the fatigue strength after implantation of the blood vessel, we established a two-way fluid-solid coupling model of the blood vessel、stent and the blood in this paper. The ANSYS finite analysis software was used in this paper to simulative analysis the fatigue performance of stent after implantation, the coupling calculation of structural solid mechanics analysis and fluid dynamics analysis is realized, and the numerical results of the stent under a blood pulsating load are obtained. According to the simulation results, the fatigue performance of the implanted stent is evaluated by Goodman criterion and dynamic safety factor. The results show that the multi-component nature of blood has a greater impact on the stress fluctuation of the stent; the thickness of the stent has almost no effect on the stress distribution of the stent, but has a greater impact on the fatigue performance.